Estimation of serum TSH receptor autoantibody concentration and affinity - Nakatake, Nobuhiro; Sanders, Jane; Richards, Tonya; Burne, Peter; Barrett, Carol; Pra, Chiara Dal; Presotto, Fabio; Betterle, Corrado; Furmaniak, Jadwiga; Smith, Bernard Rees (Thyroid (New York, N.Y.), 2006)
We have used the human monoclonal TSH receptor (TSHR) autoantibody (M22) as a labeled ligand in competition with individual patient TSHR autoantibodies (TRAb) to estimate their serum concentrations and affinities. TSHR coated tubes, (125)I-labeled M22 IgG and Fab, and patient sera IgG and Fab were used in these studies. In 15 patients with Graves' disease, TRAb concentrations ranged from 50 to 500 ng/mL of serum (5- 60 parts per million of total serum IgG) and TRAb IgG affinities from 3.0 +/- 1.0-6.7 +/- 1.54-10(10) L/mol (mean +/- SD; n=3). Fab fragment affinities were similar to those of intact IgG. Serum TRAb with blocking (TSH antagonist; 4 patients) activity had similar affinities (3.0 +/- 0.25-7.2 +/- 2.2-10(10) L/mol) to TRAb IgG from patients with Graves' disease, but blocking TRAb concentrations were higher (1.7 - 27 mg/mL of serum). The concentrations of TRAb that we observed in the sera of the 15 Graves' patient (0.33 - 3.3 nmol/L) can be compared with that of circulating TSH. In particular, a serum TSH concentration of 100mU/L (0.7 nmol/L) is in the same range as the concentrations of TRAb we observed. Such a TSH concentration (similar to that observed after injection of 0.9 mg of recombinant human TSH) would be expected to cause a similar degree of thyrotoxicosis as seen in Graves' disease. Consequently, the thyroid-stimulating potencies (i.e., activity per mol) of patient serum TRAb and human TSH appear to be of a similar magnitude in vivo as well as in vitro. Overall, our results indicate that serum TRAb affinities are high and show only limited variations between different sera whereas concentrations of the autoantibodies vary widely.